Expression of DAP-5 in HK2 cell apoptosis induced by gentamicin - GAO, Jian-jun; Zhao-yan, GU; Yong-xing, XU; Bo-ran, LIANG; Jia-mei, WEI; Yue-hua, GAO; Yu, NA (Jie fang jun yi xue za zhi, 2015)
Objective 　To reproduce a model of gentamicin induced apoptosis of human kidney epithelial cell (HK2), to observe the expression of death-associated protein 5 (DAP5) in HK2 cells, and to explore the relationship between PI3K/Akt/ mTOR signal pathway and DAP5. Methods　HK2 cells were cultured with 3.2mg/ml gentamicin. Cell apoptosis was determined by DNA agarose gel electrophoresis, the apoptotic rate was determined with flow cytometry. Protein expressions of DAP5, Akt and p-Akt were assessed with Western blotting. Rapamycin was used to block PI3K/Akt/mTOR signal pathway in HK2 cell apoptosis model, and the change in DAP5 expression was observed. Results　HK2 apoptosis appeared 24h after gentamicin treatment, and the apoptotic rate was found to be increased with the prolongation of gentamicin treatment. The apoptotic rates were 5.9%, 23.0% and 49.9%, respectively, at 24h, 36h and 72h after gentamicin treatment (P<0.05). At the same time, lysis of DAP5 protein occurred to form DAP5/p86, and the expressions of DAP